2010
DOI: 10.1002/cssc.200900161
|View full text |Cite
|
Sign up to set email alerts
|

A Polymer with a Benzo[2,1‐b;3,4‐b′]dithiophene Moiety for Photovoltaic Applications

Abstract: The characterization of a benzo[2,1‐b;3,4‐b′]dithiophene containing conjugated polymer (PBTT) is demonstrated, with regard to its photovoltaic performance. X‐ray diffraction measurements reveal that the thermal treatment results in an increased crystallinity within the PBTT:[70]PCBM network and subsequent spatial rearrangement in the film. Upon stepwise annealing, the PBTT‐based bulk‐heterojunction solar cells show an overall conversion efficiency of 2.7 % under 1 sun light illumination. The photovoltaic devic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 35 publications
0
14
0
1
Order By: Relevance
“…One-pot conversion of carbohydrates into furan derivatives (e. g., by dehydration of fructose to HMF followed by oxidation to FDCA or hydrogenolysis to DMF) has already been demonstrated in batch systems. [377] This implicates a possible three-phase (e. g., gas-liquid-liquid) operation in a microreactor in the presence of solid catalysts, where an effective method can be developed for the one-pot catalytic conversion of fructose to HMF by dehydration followed by immediate hydrogenation upon HMF extraction to the organic phase. So far, three-phase (gas-liquid-liquid) flow operation in microreactors is scarcely applied in reaction studies, [378] and thus deserves much research attention.…”
Section: The "Micro-biorefinery"mentioning
confidence: 99%
“…One-pot conversion of carbohydrates into furan derivatives (e. g., by dehydration of fructose to HMF followed by oxidation to FDCA or hydrogenolysis to DMF) has already been demonstrated in batch systems. [377] This implicates a possible three-phase (e. g., gas-liquid-liquid) operation in a microreactor in the presence of solid catalysts, where an effective method can be developed for the one-pot catalytic conversion of fructose to HMF by dehydration followed by immediate hydrogenation upon HMF extraction to the organic phase. So far, three-phase (gas-liquid-liquid) flow operation in microreactors is scarcely applied in reaction studies, [378] and thus deserves much research attention.…”
Section: The "Micro-biorefinery"mentioning
confidence: 99%
“…Dye-Sensitized Solar Cell (DSSC) dibuat dengan molekul dye, nanokristalin oksida logam dan elektrolit organik liquid [21] . Berbagai polimer dipakai untuk meningkatkan efisiensi sel PV [22] . Kedua, aspek design panel permukaan sel PV, antara lain permukaan semikonduktor multilayer [23] , permukaan berpola/ nanocone [24] , permukaan nanowire [25,26)] , dan permukaan film [23,27] .…”
Section: Pendahuluanunclassified
“…[10][11][12] Among them, benzo[2,1-b:3,4-b 0 ]dithiophene (BDT) and naphtho[2,1-b:3,4-b 0 ]dithiophene (NDT) represent promising fused thiophene-based systems, which were included in various copolymers and tested as donor materials in OSCs. [13][14][15][16][17][18][19] It has been shown that in these systems annulation lowers the HOMO energy level of the polymer, thus an improvement of air stability and higher open circuit voltages (V OC ) in OSCs were shown. Müllen et al recently reported that BDT-containing polythiophenes had low-lying HOMO energy levels and favorable aggregation behavior resulting in higher eld-effect mobilities in comparison to the polythiophene counterpart.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 OSCs of the BDT-polymer in combination with soluble fullerene derivative PC 71 BM as the acceptor gave a PCE of 2.7%. 13 To date, only one example of a BDT-containing p-conjugated oligomer is reported. In comparison to the corresponding bithiophene analogue introduction of fused rings resulted in a hypsochromic shi of the longest wavelength absorption and a lowering of the HOMO energy level which was attributed to the reduction of the effective conjugation length because of the bent structure of the BDT unit.…”
Section: Introductionmentioning
confidence: 99%